Stepping Forward, Stepping Back, and into the Unknown: An Autoethnography of Solidarity - Hanson, Cindy (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
My social position emerges from years of activism and a rural, working-class history. For decades, I have worked in adult/lifelong learning and development—inside communities and post-secondary institutions—always with the goal of achieving a more just and equitable world. While I aspire to these ideals, I have also had to learn that acts of solidarity involve learning when to step forward, when to step back, and a willingness to step into the unknown. In this autoethnography I choose a few examples from life experience that illustrate solidarity in action and what might be termed revolutionary praxis. Using examples from my work in global/international development, settler-Indigenous relations, feminism, and public transportation, I explore activism and solidarity. Finally, I offer insights into how solidarity functions in spaces of adult learning, including attention to paradoxes or attempting to “do good” while reinforcing inequalities embedded in neoliberal funding, social histories, and authority structures. Positions of solidarity require deep levels of consciousness raising. In my experience, no transformation is without challenges, risk, and acts of courage.